Inverse kinematics of manipulator using weighted fuzzy clustering method for fuzzy training data. (20th July 2009) - Agarwal, Vijayant; Nakra, B.C.; Mittal, A.P.
The inverse kinematics of redundant manipulator is considered. A model-free regression approach based on weighted fuzzy clustering method is formulated. For the adopted technique, the observed or training data pair is fuzzy instead of crisp for known value of joint variables to enhance the practicability of inverse kinematics solutions, since the real-time data collected by the sensors is generally fuzzy or vague instead of crisp. Simulation results indicate that this method has higher identifying precision and better real-time ability. Therefore, a new way for solving the inverse kinematics of manipulator for fuzzy data is proposed.